Congenital rubella syndrome (CRS) in Vietnam 2011–2012—CRS epidemic after rubella epidemic in 2010–2011. Issue 31 (17th July 2015) - Toda, Kohei; Reef, Susan; Tsuruoka, Miyuki; Iijima, Makiko; Dang, Thanh Huyen; Duong, Thi Hong; Nguyen, Van Cuong; Nguyen, Tran Hien
Abstract: Background: Rubella is endemic in Vietnam with epidemics occurring every 4–5 years. In 2011, Vietnam experienced the large nationwide rubella epidemic. During the rubella epidemic, many infants born with congenital rubella syndrome (CRS) were identified and reported from the neonatal units or cardiology departments of the national hospitals. To understand the burden of CRS, National Expanded Program on Immunization (NEPI) established sentinel CRS surveillance system. Method: Three national paediatric hospitals in Hanoi and Ho Chi Minh City (HCMC) were selected as CRS sentinel surveillance sites. Blood specimens from the infants were collected for rubella specific IgM and ELISA testing was performed at the national measles and rubella laboratory. Results: From January 2011 to December 2012, 424 infants with suspected CRS were identified and reported. Among them 406 (96%) had specimens obtained, 284 (70%) cases were IgM positive including 279 laboratory confirmed CRS and 5 Congenital Rubella Infection (CRI). 13 cases were clinically confirmed and 127 (30%) were discarded. Total 292 infants were confirmed as CRS. Of the 292 infants with CRS, 69% of mothers had a history of "fever and rash" during pregnancy, of which 85% was in the first trimester. The most common clinical defects were congenital heart disease and cataract(s). However, 81.9% of the infants had a combination of major and minor signs and symptoms. Low birth weight in full term infants with confirmed CRS was observed in 114 infants (39%). Conclusions: The newly established CRS sentinel surveillance system documented the significant burden of CRS in Vietnam and provided evidence to the policy makers for the introduction of rubella containing vaccine (RCV) into Vietnam. This report highlights the importance of countries with rubella epidemic to establish CRS surveillance rapidly in order to support the introduction of RCV into the routine Expanded Programme on Immunization (EPI) immunization.